An empirical comparison of interest rates using an interest rate model and nonparametric methods - (:unkn) unknown (ROUTLEDGE TAYLOR & FRANCIS LTD, 2003)
A continuous time interest rate model is estimated using Gaussian estimation methods of Nowman (Journal of Finance, 52, 1695-706, 1997; Asia Pacific Financial Markets, 8, 23-34, 2001) and compare forecasts of interest rates with nonparametric methods on a range of currencies. Generally it is found that the continuous time model and local linear regression perform the best. The results give further evidence to the empirical results in Saltoglu (Applied Financial Economics, 13, 169-76, 2003).
Keywords: TERM STRUCTURE